1988
DOI: 10.1002/ajpa.1330750109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of altitude on the lung function of high altitude residents of European ancestry

Abstract: The forced vital capacity (FVC), forced expiratory volume in one second (FEV), and ratio of FEV to FVC (%FEV) of 161 male and 158 female youths of European ancestry who were born at high altitudes and who were residing in La Paz, Bolivia (average altitude of 3,600 m) were examined and compared with those for lowland Europeans and highland Aymara Amerindians. FVC and FEV were significantly larger (p less than .001) in the La Paz Europeans than in two lowland control samples of European ancestry, with the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 15 publications
(26 reference statements)
5
43
1
1
Order By: Relevance
“…The FVC and FEV 1 of high altitude populations have frequently been compared to low altitude standards in order to gauge the general increase associated with either genetic adaptation or developmental adjustments to high altitude hypoxia (Frisancho, 1969;Frisancho et al, 1973;Malik and Singh, 1979;Beall, 1984;Greksa et al, 1987Greksa et al, , 1988Havryk et al, 2002;Kiyamu et al, 2012). The results of this study indicate that the inclusion of stunted children in high altitude populations compromises the validity of such comparisons.…”
Section: Discussionmentioning
confidence: 97%
“…The FVC and FEV 1 of high altitude populations have frequently been compared to low altitude standards in order to gauge the general increase associated with either genetic adaptation or developmental adjustments to high altitude hypoxia (Frisancho, 1969;Frisancho et al, 1973;Malik and Singh, 1979;Beall, 1984;Greksa et al, 1987Greksa et al, , 1988Havryk et al, 2002;Kiyamu et al, 2012). The results of this study indicate that the inclusion of stunted children in high altitude populations compromises the validity of such comparisons.…”
Section: Discussionmentioning
confidence: 97%
“…As in the study of STANOJEVIC et al [5], with the exception of English children, Caucasian children from different centres produced a higher FEV1 and FVC than their American counterparts (table 3). Mexican children produced relatively large volumes (table 3), possibly because they were born and raised at an altitude of 2,240 m [52]. In spite of a comparable TLC for Ht and age between children from Hong Kong, Australia, the Netherlands and England, the RV/TLC ratio was appreciably smaller in Australian youths, who had a larger vital capacity, for which we have no explanation.…”
Section: Anthropometry and Ethnicitymentioning
confidence: 90%
“…Although this same issue has been raised, nutrition versus hypoxia per se, it is becoming clear that (i) there is growth retardation, including at birth, of children born at high altitude; and (ii) when controlled for nutrition, socio-economic class and other factors, studies have concluded that growth and development at high altitude result in a moderate delay in linear growth of wellnourished children, and that these patterns are established very early in life. 46,47 One very interesting observation that has bearing on this issue is related to hypoxia in invertebrates. 48,49 Fruit flies (Drosophila) decrease their body size as a function of severity of the hypoxic stress.…”
Section: Discussionmentioning
confidence: 99%